Vatha suram (fever) in literatures of siddha medicine - Thayalini, T.; Prasad, V.M. (Life Science Informatics Publications, 2019)
Siddha Medicine is one of the Indigenous medical systems of Sri Lanka. It says that there are 4448 diseases can affect the humans. Suram is considered as a one of the diseases and 182 types were identified from ‘Literature review of suram(fever) in Siddha Medicine’. Vatha suram is one of the types, classified based on increase vatha dosha in human body. Causes, sign & symptoms of vatha suram are differing from literature to literature. To overcome this problem the review of the vatha suram is essential for the current world to identify the causes, classification and pathology of vatha suram, and to compare with currently facing and challenging fevers. Siddha literatures were searched from the Library of Unit of Siddha Medicine, University of Jaffna and main library of Jaffna Municipal council for suram. Thirteen books were identified and collected for this study. Data were collected, listed out and tabulated. These tabulated data were analyzed. Out of 13 literatures, only 10 Books has given the details about vatha suram. Out of 10 literatures, only 8(61.53 %) has mentioned about 17 causes. These causes are categorized based on the affecting tridatus(vatha, Pitha and kapha) through unhealthy diet and habits. Out of 10 literatures, 9 mentioned about the signs &symptoms of vatha suram. Over 50% of literatures mentioned that yawning, constipation, body heat, pain in head, chillness are the sign & symptoms of vatha suram. In Allopathy medicine, viral fever has similar symptoms of vatha suram such as body pain, joint pain and constipation. Vatha suram can be correlated with viral fever.
Keywords: Vatha Suram; Literature; Siddha Medicine; Fever